2000
DOI: 10.1097/00005392-200012000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Bacillus Calmette-Guerin and Dimethyl Sulfoxide for Treatment of Classic and Nonulcer Interstitial Cystitis:

Abstract: Intravesical BCG has been presented as a promising new option for treatment of interstitial cystitis. We failed to demonstrate benefit from this treatment. Dimethyl sulfoxide had no positive effect on maximal functional capacity but resulted in a significant reduction in pain and urinary frequency, although only in patients with classic interstitial cystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…| 1679 of pain in classic and non-classic subjects receiving DMSO, as well as a significant decrease in urinary frequency for classic IC. 24 BCG treatment showed no significant difference from baseline measures in any categories. Overall, intravesical DMSO appears to be more effective as compared to BCG in the treatment of IC/BPS.…”
Section: Randomized-controlled Trialsmentioning
confidence: 68%
See 2 more Smart Citations
“…| 1679 of pain in classic and non-classic subjects receiving DMSO, as well as a significant decrease in urinary frequency for classic IC. 24 BCG treatment showed no significant difference from baseline measures in any categories. Overall, intravesical DMSO appears to be more effective as compared to BCG in the treatment of IC/BPS.…”
Section: Randomized-controlled Trialsmentioning
confidence: 68%
“…21 Increased urgency and dysuria, lethargy, nausea, fever, and hematuria are also low-frequency adverse effects. 22,23,24 Known sideeffects have been theorized to be related to a transient chemical cystitis that occurs with intravesical DMSO instillation. 25 In contrast, Rossberger and colleagues reported that only 11% of subjects did not experience adverse events.…”
Section: Dmso History and Initial Usementioning
confidence: 99%
See 1 more Smart Citation
“…Ek et al [17] reported that, among 17 patients with Hunner lesions, DMSO improved pain and urinary frequency in 12 patients but did not improve bladder capacity. Peeker et al [18] reported that while DMSO had no positive effect on maximal functional capacity, it significantly reduced pain and urinary frequency, but only in patients with classic IC (Hunner type IC). Recently, Tomoe [19] reported the effectiveness of maintenance DMSO therapy for 24 months fol-lowing therapeutic hydrodistention in Hunner type IC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this was a very small group of patients with little information on other relevant parameters. A recent double-blind, cross-over study compared the efficacy of intravesical BCG to DMSO in 21 patients, 11 with classic and 10 with non-ulcer IC [229]. There was no demonstrable benefit with BCG treatment, while there was a significant urinary frequency decrease with DMSO in classic IC and substantial pain decrease with DMSO in both classic and non-ulcer IC [229].…”
Section: Bacillus Calmette-guerin (Bcg)mentioning
confidence: 99%